Hypoglycemic activity of Cassia javanica Linn. in normal and streptozotocin-induced diabetic rats - Urmila C Kumavat; Shraddha N Shimpi; Sandesh P Jagdale (Wolters Kluwer Medknow Publications, 2012)
In present work, one of the ornamentals and medicinally less known plant Cassia javanica has been explored for hypoglycemic potential. It aimed to check the hypoglycemic effect of C. javanica leaves on normal and streptozotocin (STZ)-induced diabetic rats by acute and sub-acute studies. Prior to the hypoglycemic study, acute oral toxicity testing of drug was performed. Later, the effects of single and multiple doses of test drug were studied using various parameters. Dried powdered leaf material was used as an oral drug. The preliminary phytochemistry of drug was done by standard qualitative tests. Diabetes was induced in rats by single intraperitoneal injection of STZ. Single and multiple doses of test drug (0.5 g/kg body weight/day) were given to normal and diabetic rats. The parameters studied were blood glucose, serum cholesterol, serum triglycerides, and serum proteins. The results of test drug were compared with standard hypoglycemic drug-glibenclamide (0.01 g/kg/day). Statistical analysis was done by 'Student's 't' test' and one way ANOVA test. In preliminary phytochemistry, antidiabetic compounds were detected. Unlike acute, subacute treatment of test drug showed highly significant reduction (37.62%) in blood glucose level of diabetic rats in ten days. This effect was considerably good in comparison with standard drug (63.51%). The test drug and standard drug exhibited insignificant change in the abnormal levels of serum metabolites of diabetic rats. Preclinically, C. javanica was proved to be effective hypoglycemic agent.